IgG4-related disease in a patient with HIV infection. Issue 4 (14th April 2019) - Ron, Raquel; Ruz-Caracuel, Ignacio; García, Eugenia; Montes-Ramírez, María Luisa
Abstract : A 47-year-old HIV-positive man with good immune and virological status presented with chronic multiple enlarged lymph nodes, lung disease and eosinophilia. Radiologic tests showed enlarged cervical, thoracic and axillary lymph nodes, with interstitial lung damage. After several non-specific histologic studies, an elevated serum IgG4 level led us to request immunohistochemistry of a lymph node sample. The test confirmed the diagnosis of IgG4-related disease.